2018
DOI: 10.1044/2017_ajslp-16-0130
|View full text |Cite
|
Sign up to set email alerts
|

Intraword Variability in Children With Cochlear Implants: The Long-Term Development up to 5 Years of Age and a Comparison With Children With Normal Hearing

Abstract: Intraword variability was characteristic of children with CI's spontaneous speech productions as it was in children with NH, and a similar factor (word length) affected variability in production. Group comparisons showed higher rates of intraword variability in children with CI, but they seemed to catch up with their peers with NH by age 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
2
10
2
Order By: Relevance
“…Results from these studies (Ertmer & Goffman, 2011;Faes & Gillis, 2018;Ingram et al, 2001; Moreno-Torres, 2014) are generally consistent; each reports increased rates of whole-word variability in children with CIs when compared to their peers matched on a variety of different variables. Ertmer and Goffman (2011) reported higher rates of variability in children with 2 years of hearing experience relative to their chronological age-matched peers, Ingram et al (2001) reported significantly higher variability in children with CIs with between 1 and 4 years of hearing experience relative to a peer group matched on phonological ability (i.e., consonant accuracy and phonemic inventory), and Moreno-Torres (2014) found greater whole-word variability in Spanish-speaking children with CIs who had 1-1.5 years of hearing experience compared to a peer group matched on expressive language ability.…”
Section: Speech Production In Children Who Use Cismentioning
confidence: 89%
See 2 more Smart Citations
“…Results from these studies (Ertmer & Goffman, 2011;Faes & Gillis, 2018;Ingram et al, 2001; Moreno-Torres, 2014) are generally consistent; each reports increased rates of whole-word variability in children with CIs when compared to their peers matched on a variety of different variables. Ertmer and Goffman (2011) reported higher rates of variability in children with 2 years of hearing experience relative to their chronological age-matched peers, Ingram et al (2001) reported significantly higher variability in children with CIs with between 1 and 4 years of hearing experience relative to a peer group matched on phonological ability (i.e., consonant accuracy and phonemic inventory), and Moreno-Torres (2014) found greater whole-word variability in Spanish-speaking children with CIs who had 1-1.5 years of hearing experience compared to a peer group matched on expressive language ability.…”
Section: Speech Production In Children Who Use Cismentioning
confidence: 89%
“…Ertmer & Goffman, 2011), and disproportionally more problems with certain phonemes such as the velar nasal and /t/ compared to their typically developing peers with NH (Flipsen, 2011). Additionally, previous studies have found increased rates of whole-word variability in monolingual children who use CIs (Chin, 2003;Chin & Pisoni, 2000;Ertmer & Goffman, 2011;Faes & Gillis, 2018;Ingram, McCartney, Bunta, Costa, & Freitas, 2001;Moreno-Torres, 2014).…”
Section: Speech Production In Children Who Use Cismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated, however, that from the findings hitherto reported it is not possible to conclude straightforwardly the existing relationship between variable articulatory movements and segmental level inconsistency (Vuolo & Goffman, 2016). Moreover, at phonemic level measures, no relationships have been found in typically developing preschool-aged children between either overall articulatory/phonological skills or phonological complexity of the target word and intra-word variability (Faes & Gillis, 2018;Macrae & Sosa, 2015;Martikainen et al, 2019). To the best of our knowledge, this factor has not previously been studied among children with SSD.…”
Section: Introductionmentioning
confidence: 91%
“…Overall intra-word variability has been reported to decrease after the toddler years among TD children (Faes & Gillis, 2018;Holm, Crosbie, & Dodd, 2007;Martikainen et al, 2019;Sosa, 2015). However, variability scores found in the studies have ranged remarkably, possibly due to differences in the phonology and syllable and word structures of the target languages, as well as in the study procedures: among 3+ years the figures vary from 12% to 62%, 4+ years from 6% to 39%, and 5+ years from 4% to 36%.…”
Section: Introductionmentioning
confidence: 92%